2009
DOI: 10.1264/jsme2.me08561
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Analysis of Bacterial and Archaeal Communities in Methanogenic Sludge Granules from Upflow Anaerobic Sludge Blanket Reactors Treating Various Food-Processing, High-Strength Organic Wastewaters

Abstract: A comprehensive survey of bacterial and archaeal community structures within granular sludges taken from twelve different types of full-scale, food-processing wastewater-treating, upflow anaerobic sludge blanket (UASB) reactors was performed with a 16S rRNA gene-based clone library method. In total, 1,282 bacterial 16S rRNA gene clones and 722 archaeal clones were analyzed, and their identities were determined by phylogenetic analyses. Overall, clones belonging to the bacterial phyla Proteobacteria (the class … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
56
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 48 publications
6
56
0
Order By: Relevance
“…The lack of Methanosarcina sp. was probably caused by the fact that they prefer higher temperatures (55-60°C, Narihiro et al 2009) than those observed in the digesters. In anaerobic digesters methanogens are dominant hydrogenotrophs since they have a lower threshold for H 2 than acetogens, and the energy that yield from the conversion of CO 2 to H 2 to methane is greater than for conversion to acetate.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…The lack of Methanosarcina sp. was probably caused by the fact that they prefer higher temperatures (55-60°C, Narihiro et al 2009) than those observed in the digesters. In anaerobic digesters methanogens are dominant hydrogenotrophs since they have a lower threshold for H 2 than acetogens, and the energy that yield from the conversion of CO 2 to H 2 to methane is greater than for conversion to acetate.…”
Section: Discussionmentioning
confidence: 95%
“…In the investigated digesters, the predominance of Methanosaeta sp. with a high affi nity for acetate, a central metabolite resulting from the anaerobic fermentation of substances (Narihiro et al 2009), indicates their success within the niche of methane production from acetate. The high abundance of the genus Methanosaeta may have also been favored by the mesophilic conditions in the digesters that covered the optimum temperature for the growth of these microorganisms .…”
Section: Discussionmentioning
confidence: 99%
“…pmoA was amplified by a seminested PCR scheme by the method of Horz et al 36) mcrA was amplified with mixed forward primer ME3MF/ME3MF-e 37) and reverse primer ME2r 021) following the protocol of Nunoura et al 37) The archaeal 16S rRNA gene was amplified with primers ARC109f 38) and ARC915r 39) by a previously described method. 40) Clone library. PCR amplicons were purified with a QIAquick PCR Purification Kit (Qiagen, Valencia, CA), and then subcloned into a pT7Blue-2 T-vector (Novagen, Madison, WI) with a DNA Ligation Kit (Takara Bio, Ohtsu, Japan) following the manufacturer's instructions.…”
Section: Methodsmentioning
confidence: 99%
“…quinone profiling, FISH, denaturing gel gradient electrophoresis (DGGE), and DNA microarray (92,162)] have been developed and applied to nitrification-denitrification (47, 105, 122), enhanced biological phosphorus removal (EBPR) (34, 160), anaerobic digestion (6,117), scum-forming (42), microbial fuel cells (18,38), reverse-osmosis water purification (8) In addition, molecular techniques revealed that most of the model organisms suggested based on the outcome of culturedependent methods are of minor relevance. One example is polyphosphate-accumulating organisms (PAOs).…”
Section: Biological Wastewater Treatment Systems: Excellent Teachers mentioning
confidence: 99%